Creating Multimodal Interactive Environment Using Augmented Reality and Natural User Interface - Bhushania, Preeti (International Journal of Computer Sciences and Engineering, 2025)
Human-computer interaction (HCI) is one of the most important issues when designing any real-time interactive system. An ideal augmented reality system must be able to combine the virtual information with the real information in a user friendly way as well as allow users to interact with the system naturally. The main objective of this article is to explore the multimodal augmented/mixed reality interfaces when designing innovative applications along with the use of Natural User Interface.